Interfering antibodies affecting immunoassays in woman with pet rabbits. Issue 7388 (8th March 2003) - Park, Adrian; Edwards, Mark; Donaldson, Mandy; Ghatei, Mohammad; Meeran, Karim
Abstract : Interfering antibodies must be considered when the clinical picture and immunoassay results do not match